HUBUNGAN ANTARA PERUBAHAN SUDUT INTERINSISAL DENGAN PERUBAHAN OVERBITE DAN OVERJET PADA MALOKLUSI ANGLE KLAS II DIVISI 1 SESUDAH PERAWATAN ORTODONTIK TEKNIK BEGG (Kajian Pada Sefalogram Lateral) - , Novarini Prahastuti; , Prof. Dr. drg. Pinandi Sri Pudyani, SU., Sp Ort.(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tooth movement is influenced by the type of orthodontic appliance that is used in the treatment of malocclusion. The Begg technique uses a bracket that produces tipping movement. The use of intermaxillary Class II elastic with anchorage bend resulting in retraction accompanied by bite opening on the anterior teeth . The palatal root torque auxillary changes the inclination of teeth through torque movement. Treatment of Angle Class II division 1 malocclusion with the Begg technique can change large of the interincisal angle, overbite and overjet that caused by a series of changes in the teeth inclination at each the end of treatment phase. The purpose of this study was determine the correlation between the interincisal angle changes with the overbite changes and the overjet changes in Angle Class II division 1 malocclusion after orthodontic treatment with the Begg technique. The study was conducted on the lateral sefalogram which obtained from 15 sample between 18-35 years old, cases of Angle Class II division 1 malocclusion which treated with the Begg technique with exctraction of four first premolars. Each of cephalogram was measured on interincisal angle, overbite and overjet before and after treatment. Angular were done to determine the interincisal angle changes with reference to the upper-lower incisor inclination, whereas linear measurements to determine the change overbite and overjet with reference to the occlusal plane. The result have of this study have shown that the interincisal angle were increased (24.53 ± 13.45), overbite (-1.33 ± 0.69) and overjet (-2.20 ± 1.27) were reduced after treatment. The Pearson product moment correlation test of the interincisal angle changes with the overbite changes have represented a relationship that was not significant (P> 0.05), and that interincisal angle changes with the overjet changes indicated a relationship was not significant (P> 0.05). Conclusion of this study have shown there is no correlation between the interincisal angle changes with the change of overbite and overjet in Angle Class II division 1 malocclusion after orthodontic treatment with the Begg technique.